Zjazd książąt śląskich z 1329 roku - Ptak, Marian J. (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The study examines documents which originated in connection with a visit by the King of Bohemia and Poland, John of Luxembourg, to Wrocław in April and May 1329. So far scholars have pointed primarily to the reduction to vassalage of successive Silesian dukes from the Wroclaw line (Bolesław III of Legnica and Brzeg) and Głogów line (Henry of Żagań, Conrad of Oleśnica and John of Ścinawa). They have stressed the pressure exerted by the Bohemian king, which the various dukes were unable to withstand. The author has attempted to take a closer look at the contents of the extant documents, particularly vassalage documents. They show that the King of Bohemia convened a congress of dukes to Wrocław, during which matters of vassalage were negotiated not only for individuals but also for the various lines. The negotiations featured a two-person ducal deputation acting as a court of arbitration. The documents list the dukes’ rights and freedoms with regard to the territories they governed and people settled there as well as the rights of the Bohemian king as the feudal lord. They also regulated the question of mutual relations between the dukes in property and other matters. Consequently, they should be viewed as the first written legislative acts fundamental and constitutional in nature, both in the various duchies and in their association referred to as the Duchy of Upper and Lower Silesia
Keywords: Jan Luksemburski (król Czech; 1296-1346); polityka; władcy; Czechy; Śląsk